2014
DOI: 10.1590/s1677-5538.ibju.2014.05.04
|View full text |Cite
|
Sign up to set email alerts
|

How many cores should be taken in a repeat biopsy on patients in whom atypical small acinar proliferation has been identified in an initial transrectal prostate biopsy?

Abstract: ARTICLE INfO ______________________________________________________________ ______________________Objective: To compare cancer detection rates according to the number of biopsy cores in patients on whom a repeat prostate biopsy was performed for atypical small acinar proliferation (ASAP). Materials and Methods:The data of 4950 consecutive patients on whom prostate biopsies were performed were assessed retrospectively. A total of 107 patients were identified as having ASAP following an initial prostate biopsy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The probability of Gleason score greater than 6, which is considered high-grade cancer, on repeat biopsy after a diagnosis of ASAP substantially varies from 8.0 to 66.7% among different studies (12,(14)(15)(16)(17)19,21,22). In the present cohort, 13 (81.3%) of the 16 cancers were diagnosed as Gleason score greater than 6 on repeat biopsy after a diagnosis of ASAP, which is higher than the rates in the preceding reports.…”
Section: Multivariate Univariate ------------------------------------contrasting
confidence: 63%
See 2 more Smart Citations
“…The probability of Gleason score greater than 6, which is considered high-grade cancer, on repeat biopsy after a diagnosis of ASAP substantially varies from 8.0 to 66.7% among different studies (12,(14)(15)(16)(17)19,21,22). In the present cohort, 13 (81.3%) of the 16 cancers were diagnosed as Gleason score greater than 6 on repeat biopsy after a diagnosis of ASAP, which is higher than the rates in the preceding reports.…”
Section: Multivariate Univariate ------------------------------------contrasting
confidence: 63%
“…This could be one reason, therefore, that small prostate volume was found to be a predictor for cancer detection in the present analysis. Actually, the rate of cancer detection was reported to rise as the number of biopsy cores was increased on repeat biopsy for large prostates in patients with a previous diagnosis of ASAP (21). The increasing number of cores would contribute to the detection of cancer on repeat biopsy after a diagnosis of ASAP, especially for patients with large prostates.…”
Section: Multivariate Univariate ------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Only ASAP multifocality seems to be systematically related to a higher risk of a positive re-biopsy. 16 Androgen hormones are necessary for the development, maintenance, and activity of the prostate gland. 7 …”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] noted that repeat biopsy directed only to the site of atypia on initial biopsy would have missed 53% of cancer cases, whereas Aglamis et al. [ 48 ] observed that cancer was detected in 67% of ipsilateral adjacent biopsy sites, and in 54% of contralateral biopsies.…”
Section: The Re-biopsy Strategy Post Asap-diagnosismentioning
confidence: 99%